MODELO DE ESTIMAÇÃO DA PRODUÇÃO DE AGREGADOS RECICLADOS DOS RESÍDUOS DA CONSTRUÇÃO CIVIL - NAYARA SEVERO PUPIN (2022)
The recycling of construction and demolition waste (CDW) is encouraged by the new principles of sustainability and circular economy. The civil construction sector realized the importance of quantifying the waste generated and planning its reinsertion into the system, however most recycling companies do not have predictability of production of recycled aggregates, compromising their sales and reverse logistics in the sector. The general objective of this work is to propose a mathematical model of the CDW recycling process in a recycling plant in Campo Grande to predict the production of recycled aggregates in time and volume, verifying the influence of variables in the process. Statistics was used as an analysis tool, using the multiple linear regression technique for data treatment. The Survey research methodology was also used, through the application of a form with the stakeholders, to understand the reasons for the little use of recycled CDW aggregate in the works/renovations. As a result, a statistical model was generated formed by the dependent variable (volume of CDW produced) and independent variables related to the production process (operating time and volume inserted in the crusher). The proposed model obtained an adjusted R² value = 0.9857, indicating that 99% of the RCC produced can be predicted from the free variables considered. With the data collected, it was also possible to estimate that 18.40% of the raw material inserted in the crusher is lost during the entire process. With the application of the Survey, it was found that most participants do not know that the city has CDW recyclers and consequently do not use the product. In order to promote the sector's reverse logistics, it is necessary to disseminate the recycled aggregates and ensure the production of the material through the predictability of CDW recycling.